Mitogen-Activated Protein Kinase Phosphatase 1 (MKP1) Negatively Regulates the Production of Reactive Oxygen Species During Arabidopsis Immune Responses - Escudero, Viviana; Torres, Miguel Ángel; Delgado Cerezo, Magdalena; Sopeña Torres, Sara; Swami, Sanjay; Morales, Jorge; Muñoz Barrios, Antonio; Mélida, Hugo; Jones, Alan M.; Jordá, Lucía; Molina, Antonio (My University, 2024)
Genetic ablation of the ¿ subunit of the heterotrimeric G protein complex in agb1-2 confers defective activation of microbe-associated molecular pattern (MAMP)-triggered immunity, resulting in agb1-2 enhanced susceptibility to pathogens like the fungus Plectosphaerella cucumerina BMM. A mutant screen for suppressors of agb1-2 susceptibility (sgb) to P. cucumerina BMM identified sgb10, a new null allele (mkp1-2) of the mitogen-activated protein kinase phosphatase 1 (MKP1). The enhanced susceptibility of agb1-2 to the bacterium Pseudomonas syringae pv. tomato DC3000 and the oomycete Hyaloperonospora arabidopsidis is also abrogated by mkp1-2. MKP1 negatively balances production of reactive oxygen species (ROS) triggered by MAMPs, since ROS levels are enhanced in mkp1. The expression of RBOHD, encoding a NADPH oxidase¿producing ROS, is upregulated in mkp1 upon MAMP treatment or pathogen infection. Moreover, MKP1 negatively regulates RBOHD activity, because ROS levels upon MAMP treatment are increased in mkp1 plants constitutively overexpressing RBOHD (35S::RBOHD mkp1). A significant reprograming of mkp1 metabolic profile occurs with more than 170 metabolites, including antimicrobial compounds, showing differential accumulation in comparison with wild-type plants. These results suggest that MKP1 functions downstream of the heterotrimeric G protein during MAMP-triggered immunity, directly regulating the activity of RBOHD and ROS production as well as other immune responses.